2023
DOI: 10.1186/s12889-023-15779-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection and vaccination uptake in men and gender-diverse people who have sex with men in the UK: analyses of a large, online community cross-sectional survey (RiiSH-COVID) undertaken November–December 2021

Abstract: Background Men and gender-diverse people who have sex with men are disproportionately affected by health conditions associated with increased risk of severe illness due to COVID-19 infection. Methods An online cross-sectional survey of men and gender-diverse people who have sex with men in the UK recruited via social networking and dating applications from 22 November-12 December 2021. Eligible participants included self-identifying men, transgende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In our study, participants with lower educational qualifications and those without employment reported lower vaccine uptake, differences that we also found in sensitivity analyses restricted to vaccine-eligible participants. Those findings mirrored COVID-19 vaccine uptake inequalities identified in the previous RiiSH survey; during that survey period (December 2021), COVID-19 vaccination was widely accessible in the United Kingdom ( 27 ). We found bisexual and straight-identifying participants also were less likely to report mpox vaccination, consistent with findings in a smaller cross-sectional study exploring mpox vaccination uptake ( 24 ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In our study, participants with lower educational qualifications and those without employment reported lower vaccine uptake, differences that we also found in sensitivity analyses restricted to vaccine-eligible participants. Those findings mirrored COVID-19 vaccine uptake inequalities identified in the previous RiiSH survey; during that survey period (December 2021), COVID-19 vaccination was widely accessible in the United Kingdom ( 27 ). We found bisexual and straight-identifying participants also were less likely to report mpox vaccination, consistent with findings in a smaller cross-sectional study exploring mpox vaccination uptake ( 24 ).…”
Section: Discussionsupporting
confidence: 69%
“…Fourth, given higher educational attainment and employment, RiiSH-Mpox participants might represent a more health-literate sample relative to national probability survey estimates in GBMSM ( 41 ). Prior RiiSH cross-sectional samples reported near universal uptake of complete COVID-19 vaccination ( 27 ). Thus, although RiiSH-Mpox participants might not be representative of all GBMSM in the United Kingdom, our study sample likely represents key groups targeted for mpox vaccination and vaccination for other sexually transmissible pathogens, such as hepatitis A.…”
Section: Discussionmentioning
confidence: 99%
“…This study used data collected by the 2022 round of the ‘Reducing inequalities in Sexual Health during the mpox outbreak’ (RiiSH-mpox) survey, part of a series of cross-sectional community-based surveys first run in 2017 13 . The RiiSH surveys focus on health and wellbeing, sexual risk behaviours, and use of SHS amongst GBMSM, and have been used to improve understanding of the factors underlying STI trends among GBMSM in the UK 14,15 . RiiSH-Mpox included questions on these core topics as well as mpox vaccine uptake during the 2022 mpox outbreak.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have identified several common factors associated with MoVAC-19 in both LGB individuals and the general population. These factors include male sex, older age, educational attainment beyond an undergraduate degree, being in a relationship, being employed, holding positive attitudes toward the safety of COVID-19 vaccines, a positive HIV status, a negative COVID-19 infection history, and having chronic physical illnesses [ 5 , 14 , 17 , 18 , 19 ]. The WHO also recommended the individuals with significant comorbidities (e.g., diabetes, heart disease, serious immunocompromising conditions, severe obesity, and pregnancy) as the high priority group for vaccination [ 20 ].…”
Section: Introductionmentioning
confidence: 99%